PENGEMBANGAN LKPD BERBASIS STORYBOARD PADA MATERI INTERAKSI SOSIAL SEBAGAI UPAYA MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR - Winarni Winarni; Eko Handoyo; Erni Suharini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Social interaction learning materials in elementary schools still tend to be conventional so that they provide less space for students to develop creativity. This study aims to determine the effectiveness of Storyboard-Based Student Worksheets (LKPD) on Social Interaction Material as an Effort to Increase Creativity in Elementary School Students. This study uses the R&D (Research and Development) development research method. This development method uses the ADDIE method. The subjects in this study were fourth-grade elementary school students. The research instrument used an expert validation questionnaire, a readability questionnaire, a creativity questionnaire, and a student response questionnaire after using the Storyboard-based LKPD. The instrument was used to determine the quality of the Storyboard-based LKPD that had been developed. The results of the study include: 1) The characteristics of this Storyboard-Based LKPD can be accessed with a smartphone; 2) Validation results from several experts, namely media experts, material experts, and language experts with an average score of 94.21% in the very valid category. The results of the readability questionnaire obtained an average score of 94.70% positive responses; 3) The increase in student creativity in the experimental class (N-Gain 0.98) with Storyboard-based Student Worksheets (LKPD) was greater than in the control class (N-Gain 0.17); and 4) The student response after using Storyboard-based Student Worksheets was 95.83%, meaning the majority of students stated that the module was feasible, practical, and easy to use in learning. Therefore, based on the research results, it can be concluded that Storyboard-based Student Worksheets on Social Interaction can enhance the creativity of elementary school students.